Ecological and human health risk associated with heavy metals in sediments and bioaccumulation in some commercially important fishes in Mahanadi River, Odisha, India - Ashish Kumar Sahu; Manjil Sangita Dung Dung; Sawan Kumar Sahoo; Showkat Ahmad Mir; Binata Nayak; Iswar Baitharu (Environmental Chemistry and Ecotoxicology, 2023)
Disposal of untreated municipality sewage, industrial wastes and agricultural runoff into the Mahanadi river causes increased heavy metals load in the river basin. The present study assesses the concentrations of heavy metals (Cr, Cd, Hg, Cu, Zn, Pb and As) in sediments and their bioaccumulation in some commercially important fishes. The potential ecological risk of heavy metals in sediments and human health risk associated with the consumption of fish accumulating heavy metals are also evaluated. The concentration of heavy metals measured followed the hierarchy as follows: Mn > Cr > Zn > Cu > Pb > As > Cd > Hg. Potential ecological risk analysis of sediment heavy metal concentrations indicated that four sites in the middle stretch poses moderate ecological risk whereas three sites in the lower stretch posed low ecological risk. Zn showed hyperaccumulation in five different fish species while Cd was observed to be the least bioaccumulative with a hierarchy of Zn > Cu > Pb > Cr > As > Cd. The demersal fish Notepterus notepterus and Clarias batrachus was observed to be the most bio-accumulative to heavy metals. Though potential human health risk assessed using Target Hazard Quotient, Hazard Index and Carcinogenic Risk was found to be within the acceptable threshold, continued disposal of heavy metals could pose a greater carcinogenic as well as non-carcinogenic risk in this region.